A QUANTIFICATION ANALYSIS OF SUBURB LAND USE AND CONSTRUCTION INTENSITY BASED ON AFAR: A CASE OF THE LAND DEVELOPMENT AROUND ZIJINGANG CAMPUS, ZHEJIANG UNIVERSITY - J. R. Shi; X. M. Zhao; F. Zheng; K. Hokao; J. Ge (International Association of Lowland Technology, 2013)
China is facing an increasing urbanization in the edge area surrounding main metropolises. This paper targets at analyzing the construction mechanism of land use planning near suburban college towns. Theories and methods such as typical case analysis, mathematical model, and space capacity analysis were used to quantify the mechanism. A typical suburban block, Zijingang Campus Town of Zhejiang University was taken as the case. Since the key index (floor are ratio) indicates the construction intension of a patch of land, it is necessary to examine its appropiate range. The analysis result shows that there are differences in architectural prosperity and urban function by means of several designs. According to the guidelines of urban master planning and urban detailed plan, the Appropiate Floor Area Ratio (AFAR) calculated and deduced based on Economic Floor Area Ratio (EFAR) and Max/Min Floor Area Ratio (MFAR) can be useful in ratifying land development intensity, predicting future tend and evaluating city planning projects.